Paired associative stimulation improves motor function in the upper extremity in chronic incomplete spinal cord injury: a corroborative study - Carl Wahlgren; Richard Levi; Magnus Thordstein (Medical Journals Sweden, 2024)
Objective: To corroborate findings suggesting that spinally targeted paired associative stimulation improves upper extremity motor function in chronic incomplete spinal cord injury. Design: Prospective interventional study. Subjects: Five adults with chronic tetraplegia. Methods: Participants received paired associative stimulation, combining peripheral nerve stimulation and navigated transcranial magnetic stimulation towards 1 arm (16 1-h sessions during 4 consecutive weeks, targeting the 3 large nerves). Manual muscle testing (MMT) was performed in 23 muscles in each arm, at 3 time points (pre-stimulation, t0; the week following the stimulation period, t1; and 4-5 weeks post-stimulation, t2). Additionally, grip strength and changes in the Canadian Occupational Performance Measure were assessed. Results: The mean improvement in manual muscle testing scores in the targeted extremity was +0.49 at t1 (p = 0.078) and +0.55 at t2 (p = 0.062). Grip strength in the stimulated extremity increased by 3.2 kg at t1 and 3.4 kg at t2, and in the non-targeted extremity by 2.2 and 3.6 kg, respectively. Performance and satisfaction increased by 2.1/2.4 points at t1, and by 2.0/1.9 points at t2. Conclusion: Paired associative stimulation improved motor function: at the group level, MMT of the stimulated hand (p = 0.06) and non-stimulated hand (p = 0.04). Most participants achieved clinically relevant improvement. Thus, the results corroborate prior studies. The method may complement conventional rehabilitation for improving upper extremity function in incomplete tetraplegia.